2016
DOI: 10.1007/s11682-016-9576-8
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness development of human primary visual cortex related to the age of blindness onset

Abstract: Blindness primarily induces structural alteration in the primary visual cortex (V1). Some studies have found that the early blind subjects had a thicker V1 compared to sighted controls, whereas late blind subjects showed no significant differences in the V1. This implies that the age of blindness onset may exert significant effects on the development of cortical thickness of the V1. However, no previous research used a trajectory of the age of blindness onset-related changes to investigate these effects. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 64 publications
3
28
0
3
Order By: Relevance
“…Despite the presence of a normal optic chiasm and postgeniculate white matter anisotropy, GUCY2D -LCA patients have a thickened striate gray matter layer. The degree of cortical thickening found in blind people is proportional to the timing 94 and severity of vision loss. 74 The GUCY2D -LCA population has somewhat better residual visual function than the comparison blind group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of a normal optic chiasm and postgeniculate white matter anisotropy, GUCY2D -LCA patients have a thickened striate gray matter layer. The degree of cortical thickening found in blind people is proportional to the timing 94 and severity of vision loss. 74 The GUCY2D -LCA population has somewhat better residual visual function than the comparison blind group.…”
Section: Discussionmentioning
confidence: 99%
“…The functional and structural reorganization of visual areas and other higher cortices after blindness are driven by complex influences from developmental, experience-dependent plasticity and degenerative factors558081. Early studies have demonstrated that onset age of blindness have significant impacts on the functional and structural architecture of blind brain, indicating developmental factors play important roles in reshaping visual areas158283. It can explain higher functional connectivity between the AI subregions and the visual streams in blind individuals who lost vision at their earlier age (i.e., the CB or EB) than those who lost vision at elder age (i.e., the LB).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the maladaptive nature of this plasticity are abundant in the auditory system, where the magnitude of cross‐modal recruitment in the deaf is inversely related to the success of cochlear implantation (Doucet, Bergeron, Lassonde, Ferron, & Lepore, ; Giraud & Lee, ; Lee et al, ). Furthermore, the fact that structural changes within the visual system are much less pronounced in the late blind (Li et al, ; Schoth, Burgel, Dorsch, Reinges, & Krings, ; Zhang, Wan, Ge, & Zhang, ) suggests that the necessary neuronal hardware is in place for successfully processing visual inputs following restoration procedures.…”
Section: Critical and Sensitive Periods For Cross‐modal Plasticity Fomentioning
confidence: 99%